From/About Latin America: Local Poetic Imaginaries for the Development of the Argentinian New Media Art Field - Adler, Yasmin (2016)
This paper seeks to explore the particular features of the conformation and expansion of the contemporary Latin American new media art field, focusing on the Argentine scene. The analysis considers some author´s hypotheses that have described the field as an isolated niche (Geert Lovink, Domenico Quaranta and Edward Shanken, among others), since its development has taken place quite independently from the one of the broader world of non-technological contemporary art. Taking those perspectives as a starting point, the article states that the intersection between art and technology around the globe has become an extensive, complex and relatively undefined territory, shaped by certain characteristics in constant struggle. These are: the convergence of multiple disciplines, media and methodologies embodied by new media artworks which complicate a fixed categorization of technological artistic practices; and artistic processes that tend to incorporate scientific and technical knowledge or artists working in collaboration with specialists from other fields, challenging the borders between the traditional artwork and the notions of machine, apparatus and experiment. Having examined these constituting aspects, the paper argues that in the Latin American context, and specially in Argentina, this situation is even more complex given 2 principles that I recognize as `identitarian´ and `institutional´. The first one is related to the imaginaries of modernization that shaped art history, science and technology in Argentina. Based on a bivalent technopoetic/political conception, the Argentine cultural sphere has been built by means of importing foreign artistic and scientific models, considered as exemplary and neutral paradigms that were uncritically introduced and pursued since the 19th century. In this sense, the mimetic repetition of exogenous models turned into a common strategy to legitimize our own practice. On the other hand, the institutional factor refers to the specific logics of creation and development of the institutions that aimed to promote new media art in our country during the last 5 decades. Despite Argentina occupies a central role in the Latin American new media art scene, it still has not been able to boost meaningful public and private policies capable of sustaining themselves over time, such as the ones implemented in countries like Mexico or Brazil. As a result, the identity and institutional factors have prevented the Argentine field from further exploring and developing its own new media artistic language. Although we have a great number of artists experimenting the various possibilities offered by technologies, we still lack critical reflection and research on the course this production is taking. Through the inquiry of certain institutional programs and contemporary new media artworks, the paper suggests a new possible way for approaching and funding our own Latin American new media art field.The analysis concludes by stating that the Latin American principle or characteristic is not necessarily reduced to expose historical and political events of the region, or to work with low technologies by dismantling and recycling all kinds of technological devices. Besides these tactics, the Latin American new media art field can also be consolidated through a discourse that assumes the local reality without reinforcing the confrontation of peripheral and core countries. According to some recent case studies that will be considered along the lines of the paper, many interesting local technology-based art often arises when artists do not attempt to speak about Latin America. Instead, they use different technologies as tools, materials and media in relation to the concepts enhanced by their work. In summary, they do not speak about the Latin American condition, but they outline a new way of thinking about it.